Pilot Study: Assessing the Expression of Serum Lactate Dehydrogenase and Peripheral Leukocyte Ratios in Canine Oral Malignant Melanoma - Ben Murray; Kelly L. Bowlt Blacklock (Veterinary Sciences, 2022)
Measurement of blood biomarkers such as lactate dehydrogenase (LDH) and peripheral leukocyte ratios have been shown to be of prognostic value in human melanoma patients. Previous veterinary studies have demonstrated that changes in these values are detectable in multiple canine cancer patients. However, to the authors’ knowledge, no studies have yet demonstrated an increase in LDH in canine oral malignant melanoma patients, nor has the effect of metastasis on LDH levels been explored. This retrospective pilot study included 18 dogs, of which 10 were healthy controls, 5 OMM patients with metastasis and 3 without metastasis. Serum LDH was measured and pre-treatment peripheral leucocyte ratios were calculated. LDH was measurable within all patient groups and a statistically significant difference in LDH levels was detected between patients with OMM and healthy controls (p < 0.05); however, no significant difference was detected between patients with or without metastatic disease. This study suggests that serum LDH levels are significantly increased in dogs with OMM compared to healthy controls, paving the way for further research to investigate the prognostic value of this biomarker.